THE ROLE OF COMMUNICATIVE APPROACH IN DEVELOPING SPEAKING SKILLS OF EFL LEARNERS - Jovliyeva Nafosat Bahodir qizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Annotation: This article examines the significance of the communicative approach in enhancing the speaking skills of learners of English as a foreign language (EFL). The communicative approach emphasizes real-life interaction, meaningful communication, and learner-centered activities rather than rote memorization of grammar rules. The study highlights how communicative language teaching (CLT) techniques—such as role plays, discussions, problem-solving tasks, and pair work—promote fluency, confidence, and motivation among students. The findings suggest that applying the communicative approach helps learners use English naturally and effectively in various contexts.